Electroacupuncture versus solifenacin succinate for female overactive bladder: study protocol for a multicentre, randomised, controlled, double-dummy, non-inferiority trial - Ping Yin; Yue-lai Chen; Xu Li; Juanjuan Li; Lumin Liu; Qian Fan; Yisheng Huai; Bingli Chen; Wenguang Hou; Junwei Hu; Sandra Teresa Chow; Shuren Ming (BMJ Open, 2024)
Introduction Overactive bladder (OAB) affects approximately 500 million people worldwide, with a higher prevalence in women than in men, significantly impacting the quality of life of female patients. Treatment options for OAB are currently limited. Previous research has proposed that electroacupuncture could be a viable treatment for OAB in women, but there is a lack of high-quality clinical evidence. This study aims to evaluate the effectiveness of electroacupuncture as a safe and efficient non-pharmacological treatment for female OAB by comparing it with solifenacin succinate.Methods and analysis This study is a multicentre, single-blind, double-dummy randomised controlled non-inferiority clinical trial involving 204 eligible female participants with OAB. Participants will be randomly assigned in a 1:1 ratio to either the electroacupuncture group (receiving electroacupuncture and placebo) or the solifenacin succinate group (receiving sham electroacupuncture and solifenacin succinate). Each participant will undergo 12 sessions of electroacupuncture (or sham electroacupuncture) treatment and solifenacin succinate (or placebo) treatment over a 4-week period. The primary outcome measure will be the percentage change in the number of micturition episodes every 24 hours at week 4 compared with baseline. Secondary outcomes will include a percentage reduction in the number of micturition episodes every 24 hours at 2th, 8th and 16th weeks of the trial, Overactive Bladder Symptom Score, number of urinary incontinence and urgency episodes every 24 hours based on a 3-day voiding diary, OAB Questionnaire, Generalised Anxiety Disorder Scale-7, King’s Health Questionnaire and Participant Self-evaluation of Therapeutic Effects. Adverse events will be monitored throughout the study. Efficacy analyses will be conducted on both the intention-to-treat population and the per-protocol set population.Ethics and dissemination Ethical approval has been obtained from the Medical Ethics Committee of Longhua Hospital Shanghai University of Traditional Chinese Medicine (approval number: 2022LCSY097). Each participant will sign a written informed consent before randomisation. The results of this study will be published in a peer-reviewed journal.Trial registration number  NCT05798403.